Influence of Cu content on physical characterization and optical properties of new amorphous Ge–Se–Sb–Cu thin films. (21st November 2018) - Hegazy, H H; Dahshan, A; Aly, K A
Abstract: The present work aims to theoretically study the effect of Cu concentration through many physical parameters, including coordination number (CN), constraints number (CON), overall mean bond energy ( ⟨ E ⟩ ), and cohesive energy (CE), for Ge25 Se65 Sb10−x Cux (where x = 0, 2.5, 5, 7.5 and 10 at%) glasses. As well, the optical constants of the thin films were evaluated via the use of the Swanepoel technique. As the Cu concentration rises, it is found that CN, CON, ⟨ E ⟩, and CE also rise. This relationship demonstrates the obvious evidence for incremental rigidity of the Ge25 Se65 Sb10−x Cux glasses with the addition of Cu. The chemical bonds anticipated within the glasses were estimated. It was revealed that the heteropolar bonds occurred in the examined glasses are Cu–Se, Ge–Se and Sb–Se, which have energies of 62.425, 49.441 and 43.981 kcal mol −1, respectively. The acquired estimations of the refractive index ( n ) of the films were fitted to the two-term Cauchy dispersion equation to get the single oscillator (Eo ) and dispersion (Ed ) energies. In addition, the estimations of the absorption coefficient ( α ) were acquired using the conditions suggested by Connell and Lewis. An energy gap ( E g ) decrement from 1.79 to 1.47 eV was prompted by a Cu concentration rise from 0 to 10% at%.